Предмет: Математика, автор: tetusnikovfanboj

помогите решить, 55 БАЛОВ

Приложения:

Simba2017: 1) ответ D
Simba2017: 2)B
Simba2017: 3)B

Ответы

Автор ответа: sangers1959
0

Пошаговое объяснение:

y'=(\frac{x^3}{3} +\frac{x^2}{2} -14)'=\frac{3x^2}{3} +\frac{2x}{2} =x^2+x.

Ответ: D. x²+x.

y'=(5*cosx-4*sinx)'=5*sinx+4*cosx+C.\\

Ответ: B. 5sinx+4cosx+C.

x(t)=7t^2+3\ \ \ \ t=2\ \ \ \ v(2)=?\\v(t)=x'(t)=(7t^2+3)'=14t.\\v(2)=14*2=28.

Ответ: B. 28.

f'(x)=((\frac{1}{9} -3x^3)^{27})'=27*(\frac{1}{9}-3x^3)^{26}*(\frac{1}{9}- 3x^3)'=\\-27*(\frac{1}{9} -3x^3)^{26}*9x^2=-243*(\frac{1}{9}-3x^3)^{26}*x^2.

Ответ: E.

f'(x)=(\sqrt{7+2x} )'=((7+2x)^{\frac{1}{2}})'=\frac{1}{2} *(7+2x)^{-\frac{1}{2} }*(7+2x)'=\\=\frac{2}{2\sqrt{7+2x} } =\frac{1}{\sqrt{7+2x} } .

Ответ: D.

Похожие вопросы
Предмет: Русский язык, автор: DashaGalushko